2014
DOI: 10.1097/ta.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacologic resuscitation on the brain gene expression profiles in a swine model of traumatic brain injury and hemorrhage

Abstract: This is the first high-throughput analysis of cerebral gene profiling following TBI + HS. It shows that treatment with VPA significantly alters early transcription of pathways related to cell survival, which may explain its neuroprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Public databases and sources used in this analysis are specified in Supplementary Table 1. These included experimental results from a swine model of TBI and hemorrhage (5,9). Other primary data included microarray expression data from postmortem human brain tissue obtained from the Human Brain Atlas of the Allen Brain Science Institute (21) and other sources (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public databases and sources used in this analysis are specified in Supplementary Table 1. These included experimental results from a swine model of TBI and hemorrhage (5,9). Other primary data included microarray expression data from postmortem human brain tissue obtained from the Human Brain Atlas of the Allen Brain Science Institute (21) and other sources (22).…”
Section: Methodsmentioning
confidence: 99%
“…VPA has been shown to be neuroprotective in animal models of traumatic brain injury (TBI) (5,6), spinal cord injury (7), and in neurodegenerative disease (8). In a swine model of TBI and hemorrhagic shock (HS) VPA decreases brain lesion size, improves neurologic recovery, and down-regulates genes associated with necrosis, apoptosis, and inflammation (9). The HDAC inhibitor, sodium butyrate, with a mechanism of action like that of VPA, has been shown to activate neurogenesis in rodent brain following ischemic injury (10).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that valproic acid may alter gene expression and protein functions following TBI (Dekker, 2014b; Halaweish, 2015b; Bambakidis 2016). Valproic acid has been in clinical use as a mood stabilizing and anti-epileptic and drug since the 1970s.…”
Section: Novel Resuscitation Techniques – Epigenetic Modulation Usingmentioning
confidence: 99%
“…We found that 1,668 probe sets mapping to 370 known genes were differentially expressed between hextend versus hextened+VPA groups. These genes were mapped to, among others, pathways related to cell death, apoptosis, and necrosis (Dekker, 2014b). These findings support our hypothesis that valproic acid alters important genes and pathways that could improve survival.…”
Section: Novel Resuscitation Techniques – Epigenetic Modulation Usingmentioning
confidence: 99%
“…Gene expression profiles for 1668 probe sets mapping to 370 known genes were found to be differentially modulated by VPA treatment in swine, with an overall attenuation of genes encoding apoptosis, cell death, and necrosis. Pathway analysis showed a significant modulation of cell signaling, dendritic cell response, and complement systems in the VPA treated animals (92). Recent data by other investigators has further clarified the mechanisms that are involved in the HDACI-induced neuroprotection.…”
Section: Mechanisms Underlying Vpa-induced Neuroprotectionmentioning
confidence: 99%